REKONSTRUKSI PEMIKIRAN EKONOMI ISLAM PADA MASA DAULAH MUGHAL: KAJIAN BERBASIS LITERATURE REVIEW - Ervina Hijrah Nirwana; Nasrullah Sapa, Mukhtar Lutfi (Jurnal Ekonomi dan Bisnis, 2025)
The Mughal dynasty is one of the major dynasties in Islamic history that made ã significant contribution to the development of an economy based on Islamic values. The economic policies implemented such as the agrarian system, taxaion, and trade, reflect the principles of justice, balance, and protection of vulnerable groups. This research aims to recontruct the thought of Islamic economists in the Mughal Daulah trought the study of relevant literature, using the literature review method, this research analyzes secondary data from various journals, and other historical document. The result show that Mughal economic policies such as zamindari, jagirdari, zakat-based taxation, kaharaj, and jizyah as well as trade regulation prohibiting usury succeeded in creating economic stability and social harmony in a multiethnic society.